Large-Conductance Calcium-Activated Potassium Channels and Voltage-Dependent Sodium Channels in Human Cementoblasts - Kamata, Satomi; Kimura, Maki; Ohyama, Sadao; Yamashita, Shuichiro; Shibukawa, Yoshiyuki (Frontiers in Physiology, 2021)
Cementum, which is excreted by cementoblasts, provides an attachment site for collagen fibers that connect to the alveolar bone and fix the teeth into the alveolar sockets. Transmembrane ionic signaling, associated with ionic transporters, regulate various physiological processes in a wide variety of cells. However, the properties of the signals generated by plasma membrane ionic channels in cementoblasts have not yet been described in detail. We investigated the biophysical and pharmacological properties of ion channels expressed in human cementoblast cell lines by measuring ionic currents using conventional whole-cell patch-clamp recording. The application of depolarizing voltage steps in 10 mV increments from a holding potential (Vh) of -70 mV evoked outwardly rectifying currents at positive potentials. When intracellular K+ was substituted with an equimolar concentration of Cs+, the outward currents almost disappeared. Using tail current analysis, the contributions of both K+ and background Na+ permeabilities were estimated for the outward currents. Extracellular application of tetraethylammonium chloride (TEA) and iberiotoxin (IbTX) reduced the densities of the outward currents significantly and reversibly, whereas apamin and TRAM-34 had no effect. When the Vh was changed to -100 mV, we observed voltage-dependent inward currents in 30% of the recorded cells. These results suggest that human cementoblasts express TEA- and IbTX-sensitive large-conductance Ca2+-activated K+ channels and voltage-dependent Na+ channels.